N2–H2 plasma functionalization of carbon fiber fabric for polyaniline grafting. Issue 8 (6th April 2020) - Ceregatti, Thayara; Kunicki, Lucas; Biaggio, Sonia R.; Fontana, Luis C.; Dalmolin, Carla
Abstract: Carbon fiber fabric was treated with radiofrequency plasma in a N2 /H2 gas mixture to create functional groups with –NH x or –N, thus promoting conditions for polyaniline (PAni) grafting. The morphology and chemical structure of PAni on the carbon fiber surface were assessed by scanning electron microscopy and Raman spectroscopy, showing strong interactions between the PAni and the carbon fiber, especially for the 5‐min plasma‐treated substrate. The electrochemical activity of electrodes consisting of carbon fiber fabric and PAni was evaluated by cyclic voltammetry and electrochemical impedance spectroscopy, which showed fast polarization response and lower charge transfer resistance for electrodes with better interactions between the PAni and the carbon fiber substrate, indicating the occurrence of grafting. Abstract : Polyaniline (PAni) was deposited on carbon fiber (CF) treated by N2 –H2 plasma. After the plasma treatment, NH x groups were inserted into the CF surface, which, during polymerization, were able to form conjugated bonds between CF and PAni. With the extension of the conjugated chain, a reduction in the charge transfer resistance was observed for charge–discharge process of PAni.